Pengaruh Media Pembelajaran Permainan Monopoli terhadap Hasil Belajar Peserta Didik Materi Kekayaan Budaya Indonesia - Lutfiah Fairuz Zahro; Iqnatia Alfiansyah; Nataria Wahyuning Subayani (Journal Innovation In Education, 2025)
This study aims to describe the effect of the use of monopoly game-based learning media on students' learning outcomes on Indonesian cultural richness materials. The background of this research is based on the need for learning media innovations that can increase students' motivation, involvement, and understanding of the material taught. The research method used is an experiment with a quasi-experimental approach. The research design applied is a non-equivalent control group design, which involves two classes as research subjects. Class IV A is designated as an experimental class that uses monopoly game learning media, while class IV C is designated as a control class that carries out learning without monopoly game media. The number of research samples was 58 students consisting of students in grades IV A and IV C at UPT SD Negeri 57 Gresik. The data collection technique uses a learning outcome test in the form of questions that are adjusted to the indicators of achievement of competence in Indonesian cultural richness materials. Data analysis was carried out using the Independent Sample T-test to determine the difference in learning outcomes between the experimental group and the control group. The results showed that the Sig. (2-tailed) value was 0.000 ≤ 0.05, which means that there was a significant difference between the two groups. Thus, the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. This indicates that the use of monopoly game learning media has a positive influence on student learning outcomes. In conclusion, monopoly games as a learning medium can be used as an innovative alternative to improve student learning outcomes, especially in understanding Indonesia's rich cultural material. This media not only makes it easier for students to receive material, but also creates a more interactive, fun, and meaningful learning atmosphere.